CHROMATOGRAPHIC SEPARATION OF BIOACTIVE COMPOUNDS FROM Ipomoea batatas lam by COLUMN, HPTLC and GC-MS TECHNIQUES - S, Nazareth Arockiamary; K, Vijayalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objective: The plant kingdom has been used for health and medicinal purposes for several thousands of years. The usage of plants to treat a variety of different ailments is universal and exists in every human culture on earth. Every plant on the planet creates specific chemical compound which is a basic part of their metabolic function. In the present study, Ipomoea batatas is targeted which is regularly used in diet, to identify its potential therapeutic property. Methods: To discover new bioactive compounds from plant sources, which can be used as new lead molecules, the Ipomoea batatas extracts was subjected to various chemical screening techniques such as Column Chromatography, high-performance thin layer chromatography (HTLC), gas chromatography-mass spectrometry (GC-MS), which quickly provides plenty of structural information, resulting in partial or complete structure determination of natural products. Results: Totally 75 fractions were collected from column chromatography and they were pooled to five fractions according to their polarity and TLC patterns, and were subjected to MTT assay. Out of which, the active fraction 3 (ethylacetate:ethanolic fraction) showed increased cytotoxicty on HepG2 cells (liver cancer cells) at IC50 (Î¼g/mL) as 33.52, compared to rest of the four active fractions of I. batatas. The chromatogram of HPTLC of active Fraction 3 (ethylacetate:ethanolic) extract of I. batatas showed four spots at the following Rf 0.45, 0.49, 0.85, 0.91 and were found to be more predominant as their area was 70.9, 315.5, 90.6, 125.0. GC-MS gave 44 compounds out of which more than 20 compounds showed medicinal property. Conclusion: It has been found that the pharmacological property shown by the active Fraction 3 (ethylacetate:ethanolic fraction) of I. batatas might be due to single compound or due to the cumulative effect of all the compounds in composite Keywords: Ipomoea batatas, Gas chromatography-mass spectrometry, High-performance thin layer chromatography